Patterned Carbon Nitride–Based Hybrid Aerogel Membranes via 3D Printing for Broadband Solar Wastewater Remediation. (23rd May 2018) - He, Peisheng; Tang, Xingwei; Chen, Liao; Xie, Peiwen; He, Lu; Zhou, Han; Zhang, Di; Fan, Tongxiang
Abstract: Controlled scalable assembly of 2D building blocks into macroscopic 3D architectures is highly significant. However, the assembly of g‐C3 N4 into tailored, 3D architectures is not yet reported. Here, a 3D printing methodology to enable the programmable construction of carbon nitride–based hybrid aerogel membranes with patterned macroscopic architectures is proposed. g‐C3 N4 nanosheets (CNNS) are used as the building block, and sodium alginate (SA) increases the viscosity of the ink to obtain the desired rheological properties. Three printing routes, including printing directly in air and in the supporting reservoirs composed of CaCl2 /glycerol solution or Pluronic F127, are demonstrated for printing versatility. The printed Au nanobipyramid–CNNS–SA hybrid aerogels exhibit broadband visible‐light absorption and superior solar wastewater remediation performance with excellent cyclic stability and easy manipulation features. Remarkably, the activity of the 3D‐printed aerogel is about 2.5 times of that of the contrast sample, attributing to the enhanced liquid velocity and solution diffusion efficiency because of the 3D‐printed structure, which is demonstrated by experimental and theoretical simulations. This approach can be extended to the macroscopic assembly of other 2D materials for myriad applications. Abstract : A 3D printing strategy is demonstrated for the programmable construction of 3D carbon nitride–based hybrid aerogel membranes. A new CN‐based ink and three printing schemes are developed to achieve pattern design control. The printed Au nanobipyramid–CNNS–SA hybrid aerogels exhibit broadband visible‐light absorption and superior solar wastewater remediation performance with excellent cyclic stability and easy separation features.